2014
DOI: 10.1167/iovs.14-13927
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of Seven Known Glaucoma-Associated Genes in Chinese Patients With Glaucoma

Abstract: Twenty-two mutations in MYOC, WDR36, OPA1, and OPTN were detected in 25 of the 683 patients with primary glaucoma, including nine MYOC mutations in 11 patients, nine WDR36 mutations in 11 patients, three OPA1 mutations in 3 patients, and one OPTN mutation in a patient who also carried a MYOC mutation. Eight mutations in MYOC, WDR36, and OPA1 in 8 of the 343 PACG patients are of uncertain significance and need to be analyzed further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 48 publications
0
50
1
1
Order By: Relevance
“…32 However, a WES study failed to detect any deleterious LTBP2 variants in Chinese POAG, JOAG, and PCG patients. 57 The prevalence of LTBP2-predicted pathogenic variants in our Australian cohort (2.8%) was lower than the rate reported in the Iranian population. Taken with the evidence from the Chinese study, the prevalence rate of LTBP2 in POAG appears to be heavily dependent on ethnicity, just like the prevalence rate of CYP1B1.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…32 However, a WES study failed to detect any deleterious LTBP2 variants in Chinese POAG, JOAG, and PCG patients. 57 The prevalence of LTBP2-predicted pathogenic variants in our Australian cohort (2.8%) was lower than the rate reported in the Iranian population. Taken with the evidence from the Chinese study, the prevalence rate of LTBP2 in POAG appears to be heavily dependent on ethnicity, just like the prevalence rate of CYP1B1.…”
contrasting
confidence: 67%
“…40,61 In a Chinese WES study, the prevalence of WDR36 variants was high and similar to MYOC; however, no controls were sequenced. 57 Our study found that WDR36 variants were the second most frequent after MYOC, although by a large margin. However, it is highly unlikely that WDR36 variants are causative for POAG in our cohort of advanced glaucoma participants given the higher prevalence of WDR36 variants in our age-matched local controls and AOGC controls than in POAG cases.…”
Section: 57mentioning
confidence: 55%
“…9 The variants detected in proband III:4 were filtered using the following steps: (1) variations predicted to affect the coding residues or mRNA splicing were selected; (2) after comparison with the 1000 Genomes Project database, variants with a minor allele frequency (MAF) o0.01 were selected; (3) variants in genes associated with ocular diseases were selected; (4) the remaining variants were compared with ethnicity-matched regional controls (195 patients with high myopia and 310 patients with hereditary retinal diseases but not glaucoma based on our unpublished data of whole exome sequencing on patients with hereditary eye diseases) to exclude ethnicity-specific polymorphisms (MAF ≥ 0.01); (5) effects of the remaining variants on coding residues of the remaining variants were analyzed using Polyphen-2 and SIFT; 15,16 (6) the remaining variants predicted to have damaging effects on coding sequence and to affect splicing were confirmed by Sanger sequencing and validated in family members, as well as in 192 normal controls. A pair of primers used to confirm the novel variant in GJA1 were designed using the Primer3 online tool (http://frodo.wi.mit.edu/primer3/): 17 GJA1-Forward 5′-aaaagagatccctgcccaca-3′ and GJA1-Reverse 5′-aggctgttgagtaccacctc-3′.…”
Section: Methodsmentioning
confidence: 99%
“…The polymerase chain reaction was used to amplify the target variants, and the amplicons were analyzed with an ABI BigDye Terminator cycle sequencing kit v3.1 (Applied Biosystems, Foster City, CA, USA) on an ABI3130 Genetic Analyzer (Applied Biosystems) as described in a previous study. 9 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation